2014
DOI: 10.1111/ceo.12329
|View full text |Cite
|
Sign up to set email alerts
|

Increased D‐serine in the aqueous and vitreous humour in patients with proliferative diabetic retinopathy

Abstract: Increased D-serine in the aqueous and vitreous humour was found in patients with PDR compared with control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…d ‐serine from retina and RPE tissue of mice was detected with reverse‐phase HPLC by a method similar to that reported (Jiang et al . ). Trichloroacetic acid (10%) was used to precipitate the tissue homogenates, which were cleared by centrifugation.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…d ‐serine from retina and RPE tissue of mice was detected with reverse‐phase HPLC by a method similar to that reported (Jiang et al . ). Trichloroacetic acid (10%) was used to precipitate the tissue homogenates, which were cleared by centrifugation.…”
Section: Methodsmentioning
confidence: 97%
“…In contrast, the physiological and pathological roles of SR/ d ‐serine in the retina are relatively scant, but SR/ d ‐serine has been implicated in diabetic retinopathy (Jiang et al . , , ). SR expression has been reported in retinal ganglion cells and glial cells (Stevens et al .…”
mentioning
confidence: 99%
“…In addition, recently Jiang et al [ 16 ] found an increased level of D-serine in the aqueous and vitreous humour of PDR patients. Earlier, the same group reported high level of serine racemase, D-serine and glutamate in the diabetic eye [ 17 ].…”
Section: Glutamatementioning
confidence: 99%
“…Our prior results indicate that increased SR expression in retina and the elevated levels of retinal/aqueous D‐serine are correlated with DR (Jiang et al . , ). In this study, we provide direct evidence that loss‐of‐function of mutation of SR protects against excitotoxicity in retina, suggesting novel therapeutic approaches to ameliorate neurodegeneration in DR.…”
mentioning
confidence: 99%